Low-cost automated cell counting module fabricated using CNC milling and soft lithography - Takanobu Takenouchi; Yuta Iijima; Kazuyo Ito; Daisuke Yoshino (HardwareX)
Cell counting is one of the basic and essential procedures that researchers in cell biology, bioengineering, and other related fields learn at the outset. Systems based on various measurement principles are commercially available, and each has its own advantages and disadvantages in terms of performance, cost, and footprint. Herein, we developed a cost-effective, scalable, and compact module that enables cell counting with reasonable accuracy, throughput, and sensitivity. This cell counting module had a size of 29 × 48 × 16 mm and a cost of $165 USD. The module can be assembled by simply inserting commercially available optical and electronic components into a housing printed by CNC milling and soft lithography. To take full advantage of this module, we built an automated cell counting system using open-source and commercially available development platforms. The module exhibited a measurement accuracy (i.e., guaranteed accuracy in the concentration range of 0–500 cells/µL) and sorting resolution (i.e., selection of particles with diameters of 5 µm and 15 µm) tolerable for cellular experiments. This low-cost and small-size module can be a sufficient replacement for a routine system in cell experiments. We anticipate our work will benefit research fields such as cell biology and bioengineering.